Influência da espiritualidade, religião e crenças na qualidade de vida de pessoas com lesão medular - Magalhães, Samira Rocha (2014)
The importance of spirituality, religiosity and beliefs to overcome difficulties has been noted. The aim of this study was to evaluate the influence of spirituality, religiosity and personal beliefs in the life quality of people who had a spinal cord injury (SCI). This is an exploratory longitudinal study with a quantitative approach, conducted in the city of Fortaleza - CE, in two phases: in the hospital and then with the same patients, in their homes, through telephone contact. The study’s target population consisted of 55 people in the hospital, but only 49 participated in the second phase. In order to meet the aims of this study, two instruments were applied; one to trace the socio-demographic and clinical profiles and the Quality of Life instrument of the World Health Organization - Module Spirituality, Religion and Personal Beliefs - WHOQOL-SRPB WHO, which features eight factors, totalling 32 items on the Likert scale, where 1 represents never and 5 indicates always. Exploratory analyzes were performed by using univariate frequency distribution, descriptive measures and the Box Plot graph. The validation of the internal consistency of the responses and calculation of the scores of the respective dimensions of scale WHOQOL-SRPB were verified in both phases of the study. The ethical aspects were observed, according to Resolution 466/12 of the National Health Council (BRAZIL, 2012), and approved by the ethics committee of the UFC with Protocol 338 980 and committee co-participant (IJF) with paragraph 348 114. The validation of the internal consistency of the responses and calculate the scores of the respective dimensions of the scale were observed in both phases of the study and proved to be excellent. The Wilcoxon T test – a non parametric test for paired samples’ comparison – was used to compare the average values of the groups (hospitalized and at home). High scores were obtained from WHOQOL-SRPB domains, in both phases, in which the ones that stood out were those related to hope and optimism, spiritual strength and faith. Regarding changes in scores for the two sides domains that demonstrated a statistically significant difference was domains, meaning in life and spiritual strength, it is believed that this difference was due to the change of environment in which the person is still going through the period adaptation. Therefore, it is expected that this study lead nurses to the reflection on the relevance of spiritual and emotional care of people with SCI and to the practice of mutual respect.